STUDY OF CORRELATION OF PLATELET INDICES IN THE MANAGEMENT OF CORONARY ARTERY DISEASE - MOHAMMED IMRAN KHAN; AIZAZ FATIMA; SURYA TIWARI (Asian Journal of Pharmaceutical and Clinical Research, 2024)
Objectives: The current study aimed to assess whether platelet parameters are associated with the severity of coronary artery disease (CAD) and may be regarded as risk factors; therefore, this study was done to evaluate platelet parameters in patients with CAD. Methods: This study was carried out in the Department of Medicine of Index Medical College, Hospital and Research Center. 60 CAD patients were enrolled in the study and were compared with 60 normal, healthy individuals of the same age. Those fulfilling inclusion and exclusion criteria were enrolled in the study, and the blood samples were analyzed for platelet indices firstly at the time of admission and then repeated following antiplatelet therapy. Results: Significantly higher concentrations of mean platelet volume (p<0.001) and platelet distribution width (p<0.001) were found in cases beforetreatment when compared with the controls. A significantly lower value of total platelet count (p<0.001) was found in cases before treatment when compared with the controls. Conclusion: Platelets have been associated with the development of cardiovascular diseases such as atherosclerosis and its severe outcomes such as acute myocardial infarction, unstable angina, and sudden cardiac death. The evaluation of platelet indices is considered an important factor in determining the functionality of platelets and is recognized as a promising risk indicator for atherothrombosis.